Marriage Cancelled, What about the Rights for Children? Analysis of the Legal Consequences of Marriage Cancellation Due to Polygamy Without Permission from the Religious Courts and Decisions Against Children's Rights - Maryana Lestari; Septhian Eka Adiyatma (The Indonesian Journal of International Clinical Legal Education, 2020)
Marriage regulations have been regulated in detail through Law No. 16 of 2019 which is a renewal of Law No. 1 of 1974 regarding marriages in several articles changed and followed by other supporting rules. In the State of Indonesia the marriage system adheres to the concept of absolute monogamy, only for the marriage of one husband and one wife. As a result of cultural and religious uniformity, there is a difference in the application of law in Indonesia, the application of national law that applies the concept of absolute monogamy is the implementation of Christian religion. Islam also contributes to the organization of marriages by regulating marriages in Presidential Instruction No. 1 of 1991 concerning the Compilation of Islamic Law (KHI), this illustrates that the contribution of Islam is recognized by the state. Knowing the word polygamy is only recognized through the rules contained in Islam, but the requirements for polygamy are permitted in Indonesia only to husbands. Opponents of a polygamy marriage are polyandri marriages, the difference is seen from the side of the husband or wife who has more than 1 partner. Although it is permissible under the applicable law all the requirements required by the state must be fulfilled as a whole, some of these requirements include obtaining permission from a legal wife or prospective wife to be combined, a statement of being able to be fair, as well as other accessible requirements in the competent authority.